DEVELOPING DIGITAL WRITING TEST FOR STUDENTS OF ENGLISH AND LITERATURE DEPARTMENT - Rika Rika; Anggraini Thesisia Saragih; Yuni Khairina (Universitas Islam Sumatera Utara, 2022)
This study was aimed at developing Digital English writing test by using Quia or Quizziz for semester 2 students in Academic Year 2021/2022. Quizizz application is a digital application that has a colorful display with animation on its interface. This writing test is to find out the students’ initial ability in writing text, such as making a simple outline and write them into a simple paragraph with main idea and topic determined by the researchers. This developing test is useful for students of English and Literature Department and developed as a pre-test for mapping freshmen students’ competency in writing. Research and Development design was used in this study, with the data used from the result of need analysis as well as interviewing the lecturers and students. The data were chosen by random sampling with the total number is 60 students of the second semester in Academic Year 2021/2022 of English and Literature Department as well as 4 lecturers of writing course.